Pocket guide to clinical microbiology - Doern, Christopher D. (ASM Press, 2018)
"With fast facts and packed with tables, this useful updated edition continues to present valuable quick-reference information to the clinical microbiology community in a small package. Along with specifics on pathogenic microorganisms, there is updated information on essential diagnostic techniques--MALDI-TOF MS and sequencing--and a greatly expanded section on susceptibility testing."--Provided by publisher